2020
DOI: 10.1097/md.0000000000021429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical remission of a critically ill COVID-19 patient treated by human umbilical cord mesenchymal stem cells

Abstract: Rationale: The COVID-19 cases increased very fast in January and February 2020. The mortality among critically ill patients, especially the elder ones, is relatively high. Considering many patients died of severe inflammation response, it is urgent to develop effective therapeutic strategies for these patients. The human umbilical cord mesenchymal stem cells (hUCMSCs) have shown good capabilities to modulate the immune response and repair the injured tissue. Therefore, investigating the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
330
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(343 citation statements)
references
References 12 publications
5
330
0
8
Order By: Relevance
“…74 Another case report of an elderly patient with severe COVID-19 in the ICU treated with MSCs for 3 days showed improvement in symptoms and a subsequent negative throat swab test 4 days later. 75 MSC transfusion was not associated with any side effects in these patients indicating that it may be a safe treatment. Of note, the gene expression profile of the recovered MSC was ACE negative and TMPRSS2 negative which indicated that it remained negative for COVID-19.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 70%
“…74 Another case report of an elderly patient with severe COVID-19 in the ICU treated with MSCs for 3 days showed improvement in symptoms and a subsequent negative throat swab test 4 days later. 75 MSC transfusion was not associated with any side effects in these patients indicating that it may be a safe treatment. Of note, the gene expression profile of the recovered MSC was ACE negative and TMPRSS2 negative which indicated that it remained negative for COVID-19.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 70%
“…Some T cell surface markers like CD3, CD4, and CD8 were increased. CT scans showed that the pneumonia was cleared [121]. Including the ground-glass opacity in the lung, the other typical diagnosis characteristic of critically ill patients was a significant decrease in lymphocytes along with the increase of neutrophils.…”
Section: Mesenchymal Stem Cell Therapy For Covid-19mentioning
confidence: 98%
“…On day 21, her vital sign showed normal. On day 21 and 23 her COVID-19 test was negative and on day 30 she was discharged from the hospital [27].…”
Section: Mesenchymal Stem Cell (Msc) Therapymentioning
confidence: 99%